Intravenous leiomyomatosis presenting as Budd–Chiari syndrome: a case report and literature review - Jingwen Gan; Xiao Ma; Jiang Shao; Jinhui Wang; Dongyan Cao (Orphanet Journal of Rare Diseases)
Abstract Background Budd–Chiari syndrome (BCS) caused by intravenous leiomyomatosis (IVL) is rare. Further reports and thorough evaluation are needed to identify and manage this disease. Method We described the case of a 49-year-old lady, exhibiting features of BCS secondary to IVL, and reviewed three other previous cases of BCS caused by IVL. Results The mean onset age of these four patients was 54.8 years. All but one (Patient No. 2) had a history of myoma, myomectomy, or hysterectomy. Abdominal pain, bloating or increasing abdominal circumference, and bilateral lower extremity edema were common symptoms. The establishment of clinical diagnoses of IVL and BCS mainly depends on clinical presentations and imaging, such as ultrasonography, computed tomography, and magnetic resonance imaging. Surgical intervention to alleviate the hepatic veins outflow obstruction is the most important treatment. Conclusions BCS caused by IVL should be considered when the inferior vena cava and right atrium lesions were detected in a patient with characteristics of BCS and a history of uterine myoma or hysterectomy. Complete tumor resection is the only curative treatment and should be performed as soon as possible.